Silicon microelectronics: where we have come from and where we are heading - Lidia Łukasiak; Andrzej Jakubowski; Zbigniew Pióro (Journal of Telecommunications and Information Technology, 2004)
The paper briefly presents the history of microelectronics and the limitations of its further progress, as well as possible solutions. The discussion includes the consequences of the reduction of gate-stack capacitance and difficulties associated with supply-voltage scaling, minimization of parasitic resistance, increased channel doping and small size. Novel device architectures (e.g. SON, double-gate transistor) and the advantages of silicon-germanium are considered, too.